Analisis Unjuk Kerja Jaringan Pensinyalan No.7 - Ningsih, Yuli Kurnia (Jurnal Teknik Elektro, 2002)
This paper analyses the performance of the signalling network No.7, based on its Grade OfService (GOS). Computer software is designed and employed, based on Visual Basic 6.0 tosimulate the Signalling Network System which is based on CCS No.7. The facilities of thissimulation software is so designed as to enable the user to change inputs, using differentvalues: number of nodes, average traffic, internode distance, routing, transmission medium,number of channel. This in turn would make it possible to analyse the efficiency of thenetwork and, hence the optimum performance desired.Keywords: Grade of Service (GoS), Routing, Message Signal Unit (MSU)